Multimorbidity in chronic conditions : public primary care patients in four Greater Mekong Countries - Pengpid, Supa; Peltzer, Karl (International Journal of Environmental Research and Public Health, 2017)
The aim of this study was to explore the prevalence, pattern, and social determinants of chronic conditions multimorbidity among chronic disease primary care patients in four Greater Mekong countries (Cambodia, Myanmar, Thailand, and Vietnam). In a cross-sectional survey, chronic disease patients accessing primary care were recruited if they had been diagnosed with any of 21 chronic conditions in the past 12 months, and were interviewed with a structured questionnaire on anxiety, depression, alcohol use, tobacco use, dietary behaviour, physical activity, and quality of life. The sample included 6236 public primary care patients (32.8% men and 67.2% women), with a mean age of 53.0 years (SD = 16.8). From 21 chronic conditions, the three most common were hypertension (37.4%), depression (34.4%), and digestive diseases (32.0%). In all, 27.4% had one chronic condition, 28.6% had two, 22.4% had three, and 21.6% had four or more chronic conditions. The percentage with the highest comorbidity was depression (47.3%), hypertension (43.4%), and digestive diseases (34.1%). The highest mean multimorbidity reported was for mental illness (4.44), kidney disease (4.11), and Parkinson’s disease (4.10), and the lowest multimorbidity for epilepsy (2.43) and cancer (2.80). Compared to those who had only one chronic condition, being male, older age, lower education, and lower quality of life were associated with having two and three or more chronic conditions. Multimorbidity is a prevalent problem among chronic condition primary care patients—a ﬁnding with implications for health care delivery, management, and research.
Journal article published in the International Journal of Environmental Research and Public Health 2017, 14, 1019
Keywords: Chronic condition; Multimorbidity; Public primary care; Greater Mekong countries; Diseases; Primary health care; Chronic diseases -- Mekong Countries